Travellers’ adherence to atovaquone/proguanil malaria chemoprophylaxis after return from endemic areas - Jenny Lea Schnyder; David Cornelis Birkhoff; Myrthe Celine Jarings; Sabine Margot Hermans; Martin Peter Grobusch; Hanna Katrien de Jong (Travel Medicine and Infectious Disease, 2025)
Background: According to current guidelines, atovaquone/proguanil (AP) malaria chemoprophylaxis is taken once daily during travel, and continued for seven days after return from malaria-endemic areas. However, pharmacokinetic data and studies on drug-sparing AP regimens suggest that AP could possibly be discontinued upon return without loss of protection. Besides being more cost-effective, shorter AP regimens may enhance adherence. We aimed to investigate adherence to the current AP chemoprophylaxis regimen during the seven days post-travel, and travellers’ preferences for potential drug-sparing AP regimens. Methods: In this cross-sectional study, adult travellers, who were prescribed AP chemoprophylaxis during a pre-travel consultation between 01-12-2022 and 01-12-2023 at the Amsterdam UMC travel clinic, were send a post-travel online questionnaire. The primary outcome was the proportion of travellers non-adherent to AP during the seven days post-travel, defined as missing one tablet or more. Secondary outcomes were non-adherence during travel, reasons for non-adherence, and AP regimen preferences. Results: The questionnaire was completed by 62 % (382/614) of contacted travellers. Of the participants, 31 % (117/382) reported non-adherence during the seven days post-travel; during stay this was 16 % (58/382). Frequently reported reasons for non-adherence were: forgetfulness, low self-perceived malaria risk, and adverse effects. An alternative AP regimen discontinuing AP upon return was deemed most appealing and easy to adhere by 73 % (276/376) of participants. Conclusions: Non-adherence was high during the seven days after return. Travellers preferred an alternative AP chemoprophylaxis regimen, allowing them to discontinue upon return. Future research shall be conducted to investigate whether AP could be discontinued upon return.